The Effect of Growing Media Composition and Eco-Enzyme Concentration on the Growth and Yield of Tomato (Lycopersicon esculentum) - Daffa Novendra Aditama; Nova Triani; Djarwatiningsih (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Growth and production of tomato (Lycopersicon esculentum) are influenced by the quality of the planting mediumand nutrient availability. This study aimed to determine the effects of planting medium and eco-enzymeconcentration on the growth and yield of tomato plants. A two-factor Randomized Block Design was used, withfactors including planting medium (soil; soil and rice husk charcoal 1:1; soil and cow manure 1:1; soil, rice huskcharcoal, and cow manure 1:1:1) and eco-enzyme concentration (0, 1, 2, and 3 ml/L). The results showed asignificant interaction between planting medium and eco-enzyme concentration on plant height from 28 to 63days after planting, number of fruits per plant, and fruit weight per plant. The best treatment was thecombination of soil and cow manure (1:1) with 3 ml/L eco-enzyme. The planting medium significantly affectedplant height at 14 to 21 days after planting, the number of leaves from 14 to 42 days after planting, and floweringage, while the eco-enzyme concentration significantly affected plant height at 14 to 21 days and the number ofleaves from 14 to 35 days after planting. The combination of organic growing media with eco-enzymes canenhance tomato growth and yield, particularly in terms of plant height, fruit number, and fruit weight per plant.These results suggest this treatment is optimal for increasing tomato growth and production by improving soilphysical, chemical, and biological characteristics.